ANALISIS KEPADATAN BULU BABI DIADEMA SETOSUM PADA KONDISI TERUMBU KARANG BERBEDA DI DESA MAPUR KEPULAUAN RIAU - Thamrin Thamrin; Yudha Januarizki Setiawan; Sofyan Husein Siregar (Program Pascasarjana Universitas Riau, 2011)
Observation was conducted to analyze the different density of Diadema setosum urchin in theseveral condition of coral reef in Mapur Island of Riau Archipelago Province, from 16 until31 July 2010. The result showed that density of urchin increase by decreasing coral cover.Density of sea urchins Diadema setosum were found 8.8 ind/m2 in the highest percentagecoral cover, i.e. 84.62%, and followed by 22.46 ind/m2 urchin in 59.74 % coral cover, and32.06 ind/m2 urchin in the condition of coral cover 35.15%. The different results amongthree research station may be coused by available of D. setosum.